The use of Islamic Stories as a Moral Education Media for Early Childhood - Faizin, Faizin; Helandri, Joni (STAI Bumi Silampari, 2023)
This study explores the use of Islamic stories for moral education in young children. It emphasizes the significance of moral education in shaping children's personalities and the role of Islamic stories in transmitting religious teachings and instilling moral values. Previous research has demonstrated that Islamic stories significantly impact moral and character development in early childhood by helping children grasp abstract concepts such as goodness, justice, honesty, and empathy. However, further investigation is required to identify the most influential elements in Islamic stories and how they can be adapted to the contemporary social and cultural environment of children in the digital age.The study employs a qualitative approach and literature analysis, analyzing various sources such as scientific journals, books, and articles to understand the impact of Islamic stories on moral education for young children. The results highlight the influence of Islamic stories in shaping moral education, emphasizing their ability to effectively convey values and create emotional connections with children. Islamic stories also contribute to the moral, emotional, and social development of children, helping them understand the consequences of their actions within the framework of Islamic values. The study identifies factors that influence moral education, including the types of stories, narrative style, characters, and emphasized values, and stresses the need for further research to better comprehend these elements and enhance the use of Islamic stories in early childhood education. The study also addresses the challenges and opportunities in implementing Islamic stories for moral education. It underscores the necessity of adapting stories to align with the social and technological context of today's children, suggesting the incorporation of modern technology and the creation of new stories that address contemporary issues. Collaboration between teachers, parents, and policymakers is emphasized to integrate Islamic stories into formal and informal education and enhance the quality of moral education for young children. In conclusion, the study highlights the significant role of Islamic stories in shaping moral and character development in young children, advocating for further research, adjustments, and innovations in utilizing these stories as a tool for moral education. The implications for teachers, parents, and policymakers are also discussed, emphasizing the importance of incorporating Islamic stories into education and supporting moral education at home. Overall, Islamic stories are regarded as valuable resources for nurturing moral and ethical character in young children.